PENGARUH KOMUNIKASI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN CIAMPEA KABUPATEN BOGOR - Yasnimar Ilyas; Muhlis Muhlis; Syaiful Anwar; Zulkifli Ramdhan (Economicus : Jurnal Ekonomi dan Manajemen, 2022)
This study aims to determine the effect of communication and compensation both partially and simultaneously on employee performance in the Ciampea District office, Bogor Regency. The results showed that: (1) The results of the partial hypothesis test proved that communication had a positive and significant effect on employee performance in Ciampea District, Bogor Regency, with a t-count of 9.133 > t-table of 2.028 and a significance value of 0.000 <0.05. (2) The results of hypothesis testing partially prove that compensation has a positive and significant effect on employee performance in Ciampea District, Bogor Regency with a t count of 8.436 > t table of 2.028 and a significance value of 0.000 <0.05. (3) The results of simultaneous hypothesis testing prove that communication and compensation simultaneously have a positive and significant effect on employee performance in Ciampea District, Bogor Regency with an F count of 111,585 > F table of 2.866 and a significance of 0.000 <0.05. (4) The results of the determination coefficient test obtained an adjusted R² value of 0.863. This proves that 86.3% of employee performance in Ciampea District, Bogor Regency is influenced by communication and compensation, while the remaining 13.7% is influenced by other variables which were not examined in this study.